The Potential of Chitosan in Nanomedicine: An Overview of the Cytotoxicity of Chitosan Based Nanoparticles - Frigaard, Julie; Jensen, Janicke Liaaen; Galtung, Hilde Kanli; Hiorth, Marianne (Frontiers in Pharmacology, 2022)
The unique properties and applications of nanotechnology in targeting drug delivery, cosmetics, fabrics, water treatment and food packaging have received increased focus the last two decades. The application of nanoparticles in medicine is rapidly evolving, requiring careful investigation of toxicity before clinical use. Chitosan, a derivative of the natural polysaccharide chitin, has become increasingly relevant in modern medicine because of its unique properties as a nanoparticle. Chitosan is already widely used as a food additive and in food packaging, bandages and wound dressings. Thus, with an increasing application worldwide, cytotoxicity assessment of nanoparticles prepared from chitosan is of great interest. The purpose of this review is to provide an updated status of cytotoxicity studies scrutinizing the safety of chitosan nanoparticles used in medicine research. A search in Ovid Medline from March 23, 1998, to January 4, 2022, with the combination of the search words Chitosan or chitosan, nanoparticle or nano particle or nanosphere or nanocapsule or nano capsule, toxicology or toxic or cytotoxic and mucosa or mucous membrane resulted in a total of 88 articles. After reviewing all the articles, articles involving non-organic nanoparticles and cytotoxicity assays conducted exclusively on nanoparticles with anti-tumor effect were excluded, resulting in 70 articles. Overall, chitosan nanoparticles included in this review seem to express low cytotoxicity regardless of particle composition or cytotoxicity assay and cell line used for testing. Nonetheless, all new chitosan derivatives and compositions are recommended to undergo careful characterization and cytotoxicity assessment before being implemented on the market.